2014
DOI: 10.2174/0929867321666140826115422
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols-Rich Natural Products for Treatment of Diabetes

Abstract: Currently, experimental and clinical evidences showed that polyphenols-rich natural products, like nutraceuticals and food supplements, may offer unique treatment modalities in type 2 diabetes mellitus (DM), due to their biological properties. Natural products modulate the carbohydrate metabolism by various mechanisms, such as restoring beta-cells integrity and physiology, enhancing insulin releasing activity, and the glucose using. Sea buckthorn berries, red grapes, bilberries, chokeberries and popular drinks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 71 publications
0
55
0
1
Order By: Relevance
“…It is reported that polyphenols-rich natural products may offer unique treatment modalities for various aspects of type 2 diabetes. 23) The particular effect will depend on the structure of the compound, and stilbenes such as resveratrol and piceatannol are polyphenols that show the most promise for beneficial health effects. We previously investigated the absorption and metabolism of piceatannol in rats, 24) and the area under the time-concentration curve for intact piceatannol was two-times higher than that of intact resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that polyphenols-rich natural products may offer unique treatment modalities for various aspects of type 2 diabetes. 23) The particular effect will depend on the structure of the compound, and stilbenes such as resveratrol and piceatannol are polyphenols that show the most promise for beneficial health effects. We previously investigated the absorption and metabolism of piceatannol in rats, 24) and the area under the time-concentration curve for intact piceatannol was two-times higher than that of intact resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Such phytomedicines are usually alternative or complementary options to treatments with synthetic drugs (Dragan et al, 2015;Olasehinde et al, 2014). However, even though considered therapeutic, some bioactive plant derivatives may have toxic properties that will cause damage to the human organism, including the induction of genetic damage (Bednarczuk et al, 2010;Düsman et al, 2012;Efferth and Grefen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for improved lifestyle interventions and new dietary strategies to prevent and treat T2DM. Evidence suggests that natural bioactives may play a role in the management of blood glucose levels, by numerous mechanisms, including their insulinotropic effects (3)(4)(5) . This aim of this research was to elucidate the potential glycaemic management properties of a range of plant derived bioactives.…”
mentioning
confidence: 99%